2003
DOI: 10.1016/s1381-1169(03)00427-8
|View full text |Cite
|
Sign up to set email alerts
|

Suitable ligands for homogeneous ruthenium-catalyzed hydrogenolysis of esters

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…There has been one further, recent development in this area. Elsevier and coworkers studied DMO hydrogenation using a broader range of catalysts, and under milder conditions than those used by Matteoli et al [112,113]. Elsevier and colleagues showed that tetra-and tri-dentate phosphines, when used in combination with [Ru(acac) 3 ], are very promising pre-catalysts for this class of reaction (Table 15.17).…”
Section: Hydrogenation Of Acids and Anhydridesmentioning
confidence: 99%
“…There has been one further, recent development in this area. Elsevier and coworkers studied DMO hydrogenation using a broader range of catalysts, and under milder conditions than those used by Matteoli et al [112,113]. Elsevier and colleagues showed that tetra-and tri-dentate phosphines, when used in combination with [Ru(acac) 3 ], are very promising pre-catalysts for this class of reaction (Table 15.17).…”
Section: Hydrogenation Of Acids and Anhydridesmentioning
confidence: 99%
“…This also raises questions about the mode of operation of the different additives, zinc having been suggested to act by enhancing the reduction of the Ru(III) precursor to Ru(II) [12]. This mode of operation would be expected to yield the reduced induction period which is observed, but does not explain the enhancement or retardation of rate depending upon substrate.…”
Section: Catalysismentioning
confidence: 99%
“…Ph ligand (Figure 1, 1) in combination with ruthenium allows hydrogenation of DMO to ethane--1,2--diol (ED) at 80 bar H 2 and 100 o C [12,13,20]. A notable example not based upon phosphines is the TriSulf Bu ligand (Figure 1, 2), which combines facial capping coordination with electron--releasing character, and allows selective hydrogenation of DMO to methyl glycolate (MG),…”
Section: Triphosmentioning
confidence: 99%
See 2 more Smart Citations